Insect species composition in an under SRI management in Tanjung Karang, Selangor, Malaysia - Rabibah Razali,; Salmah Yaakop,; Maimon Abdullah,; Siti Zafirah Ghazali,; Ameyra Aman Zuki, (Malaysian Society of Applied Biology, 2015)
The composition of the insect species during the mature stage of organic paddy fields in Tanjung Karang, Selangor, Malaysia, were investigated. All specimens were collected via three sampling methods namely sweep net, handpick and stem cut. The specimens collected were identified to the family level and when possible, to the species level. A total of 404 individuals were successfully identified from 19 families, viz. Cerambycidae, Coccinellidae (Micraspis discolor (Fabricius, 1798)). Anthomyiidae, Calliphoridae, Phoridae (Megaselia sp.), Platypezidae, Platystomatidae, Sciomyzidae, Sepsidae, Alydidae (Leptocorisa chinensis Dallas, 1852), Pentatomatidae (Scotinophara coarctata (Fabricius, 1798)), Delphacidae (Nilaparvata lugens (Stal, 1854)), Apoidae, Braconidae (Bracon hebetor Say, 1836) Ichneumonidae (Temelucha philippinensis Ashmead, 1904, Xanthopimpla sp.), Sphecidae, Trigonalidae, Pyralidae (Chilo polychrysa (Meyrick, 1932)) and Tettigoniidae. Additionally, two larval stages were identified molecularly based on COI sequences and resulted in 98% identical similarity to Chilo polychrysa using BOLD and BLAST analyses. Maximum parsimony (MP) analysis also clustered Chilo polychrysa in a monophyletic clade and was supported by a 99% bootstrap value. The abundance and composition of the dominant species collected are discussed. This is a fundamental study that investigated the diversity of insect species for future reference in insect pest management, especially in organic paddy fields.